EKSTRAKSI MINYAK ATSIRI DAUN ROSELLA (Hibiscus Sabdaíiffa L ) METODE WATER STEAM DESTILATION - Helilusiatiningsih, Nunuk; Irawati, Titik; Syahara, Muhammad Alwi (Universitas Tribhuwana Tunggadewi, 2023)
The rosella plant has antioxidant and coloring compounds that are useful for coloring and aromatic various drinks. The research aimed to study the extraction of essential oils from rosella leaves through phytochemical screening and sensory testing of the oil results. The research method used extraction of essential oil using water steam distillation, color, aroma analysis using the hedonic method, and antioxidant activity using the DPPH method. Results showed the amount of essential oils in leaves is 0.0087% in 1 kg of dry material. Rosella Leaf Oil 25% like the yellow color, 75% like it, 0% dislike it, 30% like the aroma of the leaf essential oil, 70% like it, and 0% dislike it. The antioxidant activity in rosella leaves with concentrations (ppm): of 5, 10, 25, 50, 100, and 200 ppm (22,5; 29,7; 34,9; 42,13; 44,5; 51, 4)%. A comparison or control test using ascorbic acid with the same concentration as above showed a percentage of inhibition (37,53;44,16; 51,84; 61,19; 72,45; 88,22)%. The IC 50 value of ascorbic acid (as a control) is 26.94 ppm and the IC 50 of Rosella leaf extract is 171.27 ppm, which is classified as having weak antioxidant activity in the leaves. The GC-MS results showed essential oil consists cis-3 Hexenyl Acetate (11.50%), 3-Cyclohexene-1-methanol (4.97%), 2-Propenoic acid (2.65%), Linalool 3,7-oxide (2.15%), Methyl 4-methylhexanoate (1,54%), Butanoic acid (0.54 %), 3-Methylpent-3-en-2-ol (0.25%), 1-Hexen-3-ol (0,24%).